Korelasi Kemampuan Berpikir Kritis Siswa Kelas X SMA Negeri 1 Labuhan Deli terhadap Literasi Lingkungan pada Materi Pencemaran Lingkungan - Aqila Shabira Purba; Widya Arwita (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
The low level of students' critical thinking skills has the potential to affect the level of environmental literacy. This study aims to determine the level of critical thinking skills, environmental literacy levels, positive relationships and how much critical thinking contributes to environmental literacy in grade X students of SMA Negeri 1 Labuhan Deli on environmental pollution material. The study used a quantitative approach with a correlational method on 62 students selected through a purposive sampling technique. The research instruments were essay tests and questionnaires, while the data were analyzed using the Pearson Product Moment correlation test and simple linear regression assisted by SPSS 26. The results of the prerequisite test showed that the data were normally distributed, linear, and homogeneous. Students' critical thinking skills were in the high category with a score of 72, while environmental literacy was in the high category with a score of 81. The results of the correlation test showed a very strong and positive relationship between critical thinking skills and environmental literacy (r = 0.879; p < 0.05) and a coefficient of determination of 77.3%. It was concluded that the higher students' critical thinking skills, the higher their environmental literacy. This research has implications for the importance of strengthening critical thinking skills in learning to improve students' environmental literacy.